2020
DOI: 10.1371/journal.pone.0239868
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tungsten doping on the structural, morphological and bactericidal properties of nanostructured CuO

Abstract: Copper oxide (CuO) has been broadly used in different technological and biological applications. However, based on the literature review, there are few reports describing the synthesis of tungsten doped copper oxide and its biological applications, although CuO and W (tungsten) based nanomaterials have been reportedly already synthesized. In this study we synthesized novel CuO and CuO/W (at.1%, 2% and 4%) nanoparticles and explored their tungsten content-dependent bactericide activity. In order to obtain the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…[ 134b ] Tungsten has also been doped into other antibacterial materials to optimize their antibacterial ability. [ 133,137b,140 ] For example, W 4+ doping successfully enhanced the antibacterial effect of TiO 2 by shifting the absorption spectrum of light, inhibiting the electron‐hole recombination process, and decreasing the band gap energy of TiO 2 . [ 133 ] Another study found that tungsten doping could enhance the conductivity or band gap of VO 2 .…”
Section: Research Hotspots Of Tnms In the Biomedical Fieldmentioning
confidence: 99%
“…[ 134b ] Tungsten has also been doped into other antibacterial materials to optimize their antibacterial ability. [ 133,137b,140 ] For example, W 4+ doping successfully enhanced the antibacterial effect of TiO 2 by shifting the absorption spectrum of light, inhibiting the electron‐hole recombination process, and decreasing the band gap energy of TiO 2 . [ 133 ] Another study found that tungsten doping could enhance the conductivity or band gap of VO 2 .…”
Section: Research Hotspots Of Tnms In the Biomedical Fieldmentioning
confidence: 99%
“…46,64 The band gap energy of the doped samples decreased as the crystallite size decreased, which might have been caused by reduced orientation realignment and poor crystallinity of the resulting materials. 73 The PL spectra of the samples were investigated to determine the changes in the charge-transfer efficiency and recombination rate. The PL spectra of La 2 O 3 and Mo-La 2 O 3 shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 46,64 The band gap energy of the doped samples decreased as the crystallite size decreased, which might have been caused by reduced orientation realignment and poor crystallinity of the resulting materials. 73 …”
Section: Resultsmentioning
confidence: 99%
“…3a. 56,57 The E g of NRs was extracted from absorption spectra through Tauc plot with corresponding results (Fig. 3b).…”
Section: Resultsmentioning
confidence: 99%